Is maternal weight gain between pregnancies associated with risk of large-for-gestational age birth? Analysis of a UK population-based cohort. (November 2018) - Ziauddeen, Nida; Roderick, Paul J; Macklon, Nicholas S; Alwan, Nisreen A
Abstract: Background: Maternal obesity during pregnancy increases the risk of large-for-gestational age (LGA) infant and childhood obesity. We aimed to investigate the association between maternal weight change between consecutive pregnancies and risk of having a LGA baby. Methods: A population-based cohort of routinely collected antenatal health-care data between Jan 1, 2003, and Dec 31, 2017, at University Hospital Southampton, UK, was used. No age restriction was applied, and records of all women with their first two singleton livebirth pregnancies were analysed. Regression analysis was used to examine the association between interpregnancy change in maternal body-mass index (BMI) measured at first antenatal appointment of each pregnancy and LGA (adjusted for age, ethnicity, educational qualification, infertility treatment, smoking, employment status, infant sex, gestational diabetes in current pregnancy, and interpregnancy interval). We also stratified by maternal BMI category and LGA outcome in first pregnancy. Findings: 15 940 records were analysed. 2548 women (16%) lost weight and 7607 (48%) gained weight (≥1 BMI unit) between pregnancies. LGA incidence was 7% (n=1109) in first and 13% (2106) in second pregnancies; and was 12% (315) in women who lost weight and 12% (690) in women whose weight remained stable between pregnancies compared with 14% (1101) in women who gained weight. Normal-weight and overweight women who gained weight had an increased risk of LGA after having a non-LGA baby in the first pregnancy (adjusted odds ratio 1·37 [95% CI 1·16–1·61], p<0·0001 in normal weight and 1·30 [1·02–1·65], p=0·03 in overweight). Overweight women who had a previous LGA birth were at lower risk of LGA in the second pregnancy if they lost 1 or more BMI unit (0·44 [0·23–0·85], p=0·02). Interpretation: Losing weight after LGA birth in overweight women reduces the risk of subsequent LGA, whereas gaining weight increases its risk in women with no previous history of LGA. Avoiding weight gain between pregnancies is an important preventive measure to achieve better maternal and offspring outcomes. Funding: Supported by a University of Southampton Primary Care and Population Sciences PhD studentship (to NZ), theAcademy of Medical Sciences, and the Wellcome Trust (grant no: AMS_HOP001\1060 to NAA ).